2013
DOI: 10.1063/1.4829707
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the model by Klapper for 4H-SiC homoepitaxy on vicinal substrates

Abstract: 4H-SiC homoepitaxial layers free of basal plane dislocations (BPDs) are urgently needed to overcome the so-called bipolar degradation of high-voltage devices. BPDs being present in substrates are able to either propagate to the epilayer or convert to harmless threading edge dislocations (TEDs) in the epilayer. The model by Klapper predicts the conversion of BPDs to TEDs to be more efficient for growth on vicinal substrates with low off-cut angle. This paper aims to verify the model by Klapper by an extensive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The increasing demand for high performance and low cost SiC‐based devices is driving the development of epitaxy towards lower off‐cut angle substrates. This is motivated by the expected increase of the conversion rate of basal plane dislocations (BPDs) to threading edge dislocations and consequently, a reduction of the BPD density in epilayers using lower off‐cut angles . During long term forward operation of SiC bipolar devices using epilayers grown on off‐cut substrates, formation of stacking faults (SFs) results in an increased forward voltage drop which causes degradation of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand for high performance and low cost SiC‐based devices is driving the development of epitaxy towards lower off‐cut angle substrates. This is motivated by the expected increase of the conversion rate of basal plane dislocations (BPDs) to threading edge dislocations and consequently, a reduction of the BPD density in epilayers using lower off‐cut angles . During long term forward operation of SiC bipolar devices using epilayers grown on off‐cut substrates, formation of stacking faults (SFs) results in an increased forward voltage drop which causes degradation of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The dislocations we observe display a similar contrast and are nearly parallel to the c-axis. The threading dislocations parallel to the c-axis in 4H-SiC that have been reported [5,6] are either screw dislocations or edge dislocations displaying a Burgers vector along 1120. We discard the screw dislocation case because it is such that h.b = 0, h being the diffraction vector (perpendicular to the 4040 planes) and b the Burgers vector (parallel to c), and therefore, these dislocations should not be observed because they produce nearly no contrast in the image [16].…”
Section: Discussionmentioning
confidence: 95%
“…When this distance D is in the range 50-250 µm, we observe a weak (~µradian) distortion of the region lying between parallel dislocations with opposite Burgers vectors. Dislocations in 4H-SiC crystals have been extensively studied through X-ray diffraction Rocking Curve Imaging (see for instance [4][5][6][7][8][9]). The faint distortion we observe had not been investigated previously because there was no available experimental technique allowing its visualisation.…”
Section: Introductionmentioning
confidence: 99%
“…It could be shown that the harmful BPDs can be converted into non‐dangerous threading edge dislocations (TED) during the epi‐process. The experimental findings could be explained by the so‐called Klapper model, showing that the off‐cut angle of the vicinal substrates is one of the most important parameters for improving BPD conversion. Based on experimental and theoretical results from different groups worldwide the off‐cut angle of the vicinal substrates was changed during that time in the whole SiC industry from 8° to 4° because of the related increase of the conversion probability for BPDs into TEDs during the epitaxial growth.…”
Section: Development Of Wide Bandgap Semiconductors (Sic Gan Aln)—cmentioning
confidence: 98%